Emerging applications of stereotactic body radiation therapy for head and neck cancer. Issue 9 (September 2011) - Siddiqui, Farzan; Raben, David; Lu, Jiade J; Grecula, John C; Lo, Simon S; Huang, Zhibin; Mayr, Nina A; Teh, Bin S; Yao, Min
Head and neck cancer is typically managed with surgery, radiation therapy, chemotherapy or various combinations of the above. In patients who develop recurrence after radiation therapy, treatment options are limited. Reirradiation can be offered but the amount of additional radiation that can be given is limited and there is an increased risk of serious complications. Stereotactic radiation therapy has been used as a boost or salvage therapy at recurrence for nasopharyngeal carcinoma. The use of stereotactic body radiation therapy for head and neck cancer has expanded to include sites outside of the base of skull region, especially in the recurrent setting, and clinical data are emerging. This article will highlight some of the technical and clinical advances in this area.